Effectiveness of Village Funds in Reducing Rural Poverty: Panel Data Analysis of 33 Provinces - Andiatma, Farandika Gita; Yustika, Ahmad Erani; Syahfitri, Wildan (Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to examine the effect of Village Fund (VF), Village Fund Allocation (VFA), Gross Regional Domestic Product (GRDP), and Village Development Index (VDI) on the reduction of rural poverty levels across 33 Indonesian provinces during the 2015–2023 period. This quantitative research uses longitudinal panel data for 33 provinces over eight years (2015–2023), resulting in 264 observations. Given the characteristics of persistent dependent variables in dynamic models, the estimation method employed is the Two-Step Difference Generalized Method of Moments (GMM). The results confirm that VF, VFA, GRDP, and VDI simultaneously and partially exert a significant negative influence on rural poverty reduction. Notably, GRDP (coefficient -7.5173) and VDI (coefficient -4.1816) demonstrate the largest quantitative impact on poverty reduction. The government should reformulate the VF allocation formula to emphasize poverty criteria (equalization grant) and encourage the shift of village spending priority from physical infrastructure towards human capacity and economic empowerment, aligning with Amartya Sen’s capability approach. This research addresses the gap in longitudinal studies by utilizing a comprehensive set of variables (VF, VFA, VDI, and GRDP) at the national scale (33 provinces, 2015–2023), providing a robust empirical contribution to the effectiveness of Indonesia’s deep fiscal decentralization policy.